2010
DOI: 10.1007/s10549-010-0988-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated TRF2 in advanced breast cancers with short telomeres

Abstract: Introduction Telomere repeat binding factor 2 (TRF2) binds directly to telomeres and preserves the structural integrity of chromosome ends. In vitro models suggest that expression of TRF2 protein increases during mammary cancer progression. However, a recent study has reported that TRF2 mRNA levels tend to be lower in clinical specimens of malignant breast tissue. Here, we conduct the first large scale investigation to assess the levels and cellular localization of the TRF2 protein in normal, pre-malignant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Rather, we observed a decrease in TRF2 protein level with prolonged treatment of MST-312. Increased TRF2 mRNA expression could be a feedback response to telomere dysfunction as a recent study has shown that a higher level of TRF2 observed in advanced cancer cells with critically short telomeres may be important for the protective function of telomeres [43]. While a gradual telomere shortening was observed in MCF-7 cells following telomerase inhibition, a decrease in telomere length was observed 5 days after treatment with telomerase inhibitor in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, we observed a decrease in TRF2 protein level with prolonged treatment of MST-312. Increased TRF2 mRNA expression could be a feedback response to telomere dysfunction as a recent study has shown that a higher level of TRF2 observed in advanced cancer cells with critically short telomeres may be important for the protective function of telomeres [43]. While a gradual telomere shortening was observed in MCF-7 cells following telomerase inhibition, a decrease in telomere length was observed 5 days after treatment with telomerase inhibitor in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As TRF2 is essential for telomere protection, this rather early effect on telomere length could also be due to telomere deprotection due to a decrease in TRF2 expression in MDA-MB-231 cells. Studies performed in breast tissue arrays demonstrated a significant inverse relationship between a high expression of TRF2 protein and short telomeres within invasive breast carcinomas [43]. Since TRF2 inhibits telomerase and prevents activation of DNA damage response at the telomeres, the high level of TRF2 at short telomeres reflects the increased DNA repair capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections were processed according to a routine immunohistochemical staining procedure. 42 The Ki-67 primary antibody (1:50 dilution of H-300; Santa Cruz Biotechnologies) was applied to the tissue sections for overnight incubation at 4°C. Omission of the primary antibody was included as a negative control for each specimen.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…First, by reducing the amount of TRF2 at telomeres, targeted depletion of TRF2 may activate DNA checkpoint and render cells vulnerable to apoptosis. Previous studies have shown that TRF2 is highly expressed in a range of tumors including breast cancers (Diehl et al, ), colorectal carcinomas (Dong et al, ) and epithelial cancers (Blanco et al, ). Our analysis of the TCGA database indicated that the gene encoding TRF2 ( Terf2 ) is not mutated or deleted in GBM patients.…”
Section: Discussionmentioning
confidence: 99%